Optimal Sizing of UPQC to Mitigate Power Quality Issues Using ANF Controller - Vadivu U., Senthil; K. Keshavan, B. (International Journal of Engineering and Technology, 2018)
A design of compact converter based Unified Power Quality Conditioner (UPQC) is proposed to alleviate the power quality issues on both linear and non-linear load by means of a four switch three phase series and shunt converter with DC link capacitor. DC-link voltage regulation is obtained by Photovoltaic based boost converter. The recommended four switch converter system not only reduces the switching losses but also the cost of the converter as well as it reduces the number of active elements.Â Balancing of capacitors leg, filters and transformer are chosen based on the amount of sag and swell magnitude. The proposed scheme is implemented using sinusoidal pulse width modulation, simple space vector pulse width modulation and PI-Fuzzy control strategy to verify power quality issues like sag, swell and harmonics compensation added with the control performances. The performance of the optimized system is validated through simulations using MATLAB/SIMULINK.Â Â